"Incest and the Maintenance of Episcopal Consensus in the" Vita s. Albini - Halfond, Gregory I. (Journal of early Christian studies, 2023)
Usually dated among the earliest of Venantius Fortunatus's hagiographical works, the Vita s. Albini describes a dispute between Bishop Albinus of Angers and his episcopal colleagues at an ecclesiastical council. At the council, the saintly bishop was forced to lift an order of excommunication that he had placed upon an unnamed layperson guilty of incest. While modern scholars occasionally have attempted to identify this event with known Gallo-Frankish councils of the mid-sixth century, the information supplied by the Vita does not, in fact, support a secure identification, leaving open the possibility that the confrontation took place at an otherwise-unknown council ca. 536/7-42. Further complicating previous efforts to contextualize the dispute has been a general neglect of the narrative's compositional context. Writing in the aftermath of a case of royal incest that occurred in late 567 c.e., Fortunatus seems to have had this specific case in mind in composing his narrative, utilizing a conflict by then safely in the past as a literary device to address a current and controversial problem: the pressure exerted by secular elites to divert bishops from their corporate moral imperatives. The hagiographer cast Albinus himself in a role analogous to that of Bishop Germanus of Paris, who recently had risked martyrdom in excommunicating King Charibert I, following a failed conciliar effort to convince the king to end his uncanonical marriage. Fortunatus thus explored through Albinus's experiences the real difficulties facing bishops who were expected as a consequence of their membership in a common ordo to serve as spiritual counselors to the powerful.